Peningkatan Kualitas Proses Bisnis pada Unit Usaha Kerupuk di Kecamatan Krembung Kabupaten Sidoarjo - Limanto, Susana; Soesanto, Daniel; Prijambodo, Bambang; Liliana, Liliana (Warta LPM, 2023)
Crackers are one of the food commodities favored by Indonesian people. Most of the cracker business actors are MSMEs. The main problem faced by many MSMEs is the lack of business knowledge, so they are often inferior to manufacturing businesses. The same thing was experienced by MSME crackers in Krembung District, Sidoarjo which was managed by Mr. Abdul Ghofur. In this service activity, the University of Surabaya Informatics Engineering has an assistance program through technology, to expand the market share that can be reached and help MSME financial management. The programs carried out are the development of an online market place information system that is integrated with the financial system. The activity begins with program socialization and problem analysis. After that, it is followed by application development, training, mentoring, as well as observation and evaluation. Finally, reflection is carried out for the continuation of further activities. The duration of this community service activity is eight months, including one month of assistance to ensure that MSME personnel are able to use the system properly. During the mentoring process, business processes at MSMEs can run more smoothly, where sales transactions are more centralized in the system, stock records are better, and owners can get financial information more accurately and easily. Therefore, it can be concluded that this community service activity went well and helped Mr. Abdul Ghofur's MSME business processes. Service activities will be developed by providing supplies in the form of digital marketing so that MSMEs can reach new customers to access this application.